Molecular confirmation of primary monophasic synovial sarcoma of the mandible: diagnosis and management. Issue 7 (September 2022) - Donohoe, E.; Martin, D.; Faul, P.; O'Sullivan, M.J.; Barry, T.
Abstract: Synovial sarcoma (SS) is a rare, high-grade, soft tissue malignancy that originates from pluripotent mesenchymal stem cells. Knox introduced the term 'synovial sarcoma', noting its histological similarity to synovial tissue. SS is seen most frequently in young and middle-aged adults with an equal sex distribution. Symptoms are non-specific and relate to the local effect of the mass. Currently, we know of no specific guidelines for the management of SS in the head and neck. We report a case of primary monophasic SS of the mandible in a 59-year-old male, and outline our diagnostic approach and management.